Rancang Bangun Virtual Tour Sebagai Media Promosi Wisata Infinity Pool Di Agrowisata Tepas Papandayan (ATP) Berbasis Web - Dini Destiani Siti Fatimah; Yeni Pariyatin; Dikri Ramadhan (Jurnal Algoritma, 2026)
Tepas Papandayan Agrotourism is one of the lesser-known natural tourist destinations in Garut Regency, largely due to a lack of informational and promotional materials capable of attracting tourists. This study aims to develop an informative promotional medium based on 360-degree virtual tour technology that can be accessed via a website, with the goal of providing an engaging and informative virtual exploration experience. The application was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, content gathering, development, testing, and distribution. Testing employed a black-box testing approach using decision tables with test cases to ensure all functions operate correctly without errors as per the design, followed by beta testing using User Acceptance Testing (UAT) with purposive sampling to ensure the application meets user needs. The results of this study indicate that the interactive virtual tour application is now accessible and provides tourism information, serving as a promotional tool. A survey of 139 prospective tourists revealed that 97.1% of those who used the application expressed interest in visiting.